1) a² + ab - 5a - 5b = a(a + b) - 5(a + b) =
= (a + b)(a - 5)
2) a² - b² - a + b = (a - b)(a + b) - (a - b) =
= (a - b)(a + b - 1)
3) a² - b² + a + b = (a - b)(a + b) + (a + b) =
= (a + b)(a - b + 1)
3) x² + 8х= -16 - 2x 4) х² + х - 2 = 2 - 2x
х²+8х+16+2х=0 х² + х - 2-2+2х=0
х²+10х+16=0 х²+3х-4=0
Д=в²-4ас Д=в²-4ас
Д=10²-4*1*16 Д=з²-4*1*(-4)
Д=36 Д=25
1) a² + ab - 5a - 5b = a(a + b) - 5(a + b) =
= (a + b)(a - 5)
2) a² - b² - a + b = (a - b)(a + b) - (a - b) =
= (a - b)(a + b - 1)
3) a² - b² + a + b = (a - b)(a + b) + (a + b) =
= (a + b)(a - b + 1)